2003
DOI: 10.1103/physrevd.68.104023
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional gravity with torsion as a Chern-Simons gauge theory

Abstract: We show that topological 3D gravity with torsion can be formulated as a Chern-Simons gauge theory, provided a specific parameter, known as the effective cosmological constant, is negative. In that case, the boundary dynamics of the theory corresponding to anti-de Sitter boundary conditions is described by a conformal field theory with two different central charges.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(76 citation statements)
references
References 24 publications
4
70
0
Order By: Relevance
“…In consequence, the asymptotic symmetry of three-dimensional gravity with torsion (which implies α + β = 0) and gauge group SO(1, 2) × SO(1, 2) [21] is always smaller than SO(1, 2). Therefore, in this case the Lorentz symmetry cannot be preserved asymptotically, resulting in a Lorentz anomaly in the dual quantum theory.…”
Section: Non-abelian Anomalymentioning
confidence: 99%
“…In consequence, the asymptotic symmetry of three-dimensional gravity with torsion (which implies α + β = 0) and gauge group SO(1, 2) × SO(1, 2) [21] is always smaller than SO(1, 2). Therefore, in this case the Lorentz symmetry cannot be preserved asymptotically, resulting in a Lorentz anomaly in the dual quantum theory.…”
Section: Non-abelian Anomalymentioning
confidence: 99%
“…In particular, it was shown that: (a) the Mielke-Baekler model in Minkowskian spacetime possesses the black hole solution, and (b) for suitable boundary conditions, its asymptotic symmetry is described by two independent Virasoro algebras with different central charges [13,16,17,19]. One is now tempted to use this Minkowskian asymptotic structure and calculate the black hole entropy in the manner of Strominger [10].…”
Section: Introductionmentioning
confidence: 99%
“…More compactly, by representing f using its Weyl ordered symbol f (q, k), one has 17) that is, the trace operation maps the Kleinian k to −ν inside the symbol. In critical limits, one has STr Aq(2;ν) Aq 18) which means that in critical limits the model is truncated to…”
Section: Jhep01(2016)173mentioning
confidence: 99%